On the Unethical Use of Privileged Information in Strategic Decision-Making: The Effects of Peers’ Ethicality, Perceived Cohesion, and Team Performance - Johnson, Kevin J. (Journal of business ethics, 2018)
In order to make strategic decisions and improve their firm’s performance, top management teams must have information on the competitive context in general, and the firm’s competitors in particular. During the decision-making process, top managers can have access to “privileged information”—i.e., information of a confidential and potentially strategic nature that could ultimately confer a decisional advantage over competing parties. However, obtaining and using privileged information in a business context is often illegal—and if not, is usually deemed unethical or “against the rules.” Using a quasi-experimental design, this study explores the reasons why an individual might engage in such unethical behavior. We assess the extent to which managers use privileged information with respect to perceived team cohesion and peers’ ethicality. More specifically, our results show that the use of privileged information is predicted by the decision-maker’s perceptions of their team cohesion and their peers’ ethicality. Moreover, we find that team performance, as a group-level nonself-reported factor (measured by the firm’s share price in our simulation), moderates the relationship between cohesion and the use of privileged information. The relationship between cohesion, ethical behavior, and team performance is also discussed. We draw on these findings to make some practical suggestions on how to incorporate practices that could better prevent the unethical use of privileged information in strategic decision-making processes.